Performa Produksi F1 Antara Ras Pedaging × Kampung dan Kampung × Ras Pedaging pada Umur 0-12 Minggu - Darwati, S.; Sumantri, C.; Pratiwanggana, A. T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Kampung chicken is Indonesian native chicken that potential to be developed as commercialchicken.  The large-scale breeders less interest to breed kampung chicken because it has slow growth toreach slaughter weight than commercial meat type. Therefore, kampung chicken’s performance needto be improved by crossing with commercial meat type that has fast growth. This research purposedto observed the effect performance of first generation (F1) from commercial meat type crossing withkampung and their reciprocal.  Research conducted performance of crossing chicken in age 0-12 weeksage. T test used for knowing difference body weight mean, body weight gain, feed consumption, and feedconvertion rate.  The result of this research were not significant between KB cock with BK cock andKB hen with BK hen on body weight, body weight gain, feed consumption, and feed convertion rate.Whereas mortality percentage BK chicken was higher than KB chicken althought less of mortality.  KBand BK cocks had better performance than hens. Reciprocal crossing between kampung chicken andcommercial meat type had performance better than kampung chicken, so crossing had been increasedgenetic quality of kampung chicken.